CHARACTER EDUCATION IN ELEMENTARY SCHOOL-AGE CHILDREN IN INDONESIA AND JAPAN - Setiawati, Sulis; Fitri.H, Ayu; Suparman, Tarpan; Isyanto, Puji; Giri.P, Anggy; (Kawakami Harue), 川上はる江 (INFOKUM, 2022)
This article aims to compare character education policies in elementary schools in two countries, namely Japan and Indonesia and the impact of these policies on elementary schools in the two countries. This article is motivated by the fact that Indonesia is one of the most densely populated countries in the world. This is because Indonesia has not been able to control the number of births in Indonesia. Therefore, efforts should be made to foster creativity by improving the quality of education. This is because Indonesia is a developing country, so it cannot be separated from the process of improving the quality of education. This research is research with research and development method . The implementation of character education in Japan places more emphasis on practice, while in Indonesia it is still dominantly focused on theory. The Indonesian education system prioritizes students' cognitive wealth, such as academic grades, test scores, and other daily test scores. The Indonesian education system does not prioritize affective and cognitive aspects.